(3efgGL GdHjGf ajeG jSJYedg GdGfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3GdMeO dgd GdPj XgQJ HOGFY eUfhYGJg hdeG CfYe HbHhd GdcJGH dGPj SejJg HJbhje GdGHOGf HGOQJ HJQJjH cJGH KGf SejJg HfegGL GdHjGf s
(3BNQgG (B:s
(3jfJhf gh GdfGaSjG Cj UeZ GdSPGH GdLHdj hgh eGQ jGHS jSgd GdHdZe Je s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs